已知 $a > b, c > d, \frac{\mathrm{e}^a}{a+1}=\frac{\mathrm{e}^b}{b+1}=1.01,(1-c) \mathrm{e}^c=(1-d) \mathrm{e}^d=0.99$, 则
$ \text{A.} $ $a+b > 0$ $ \text{B.} $ $c+d > 0$ $ \text{C.} $ $a+d > 0$ $ \text{D.} $ $b+c > 0$
【答案】 AD

【解析】 $\because \mathrm{e}_{a+1}^a={ }_{b+1}^{e^b}=1.01 > 0$,
$
\therefore a > -1, b > -1 \text {, 令 } f(x)=\frac{\mathrm{e}^x}{1+x}(x > -1) \text {, }
$

则 $f^{\prime}(x)=\begin{gathered}x \mathrm{e}^x \\ (1+x)^2\end{gathered}$, 所以 $f(x)$ 在 $(-1,0)$ 上单调递减, 在 $(0,+\infty)$ 上单调递增, 且 $f(0)=1$,
故 $a > 0,-1 < b < 0$.
今 $h(x)=\ln f(x)-\ln f(-x)=2 x-\ln (x+1)+\ln (-x+1), x \in(-1,1)$,
则 $h^{\prime}(x)=2-\frac{1}{x+1}+\frac{-1}{-x+1}=2-\frac{2}{1-x^2} < 0$,
所以 $h(x)$ 在 $(-1,1)$ 上单调递减, 且 $h(0)=0$,
$\because b \in(-1,0), \therefore \ln f(b)-\ln f(-b) > 0, \therefore f(b) > f(-b), \therefore f(a) > f(-b), \therefore a > -b$, 即 $a+b > 0$, 故选 项 A 正确;
$$
\because(1-c) \mathrm{e}^c=(1-d) \mathrm{e}^d=0.99 > 0, \therefore c < 1, d < 1 \text {, 今 } g(x)=(1-x) \mathrm{e}^x(x < 1) \text {, }
$$
则 $g^{\prime}(x)=-x \mathrm{e}^x$, 所以 $g(x)$ 在 $(-\infty, 0)$ 上单调递增, 在 $(0,1)$ 上单调递减, 且 $g(0)=1$, 故 $0 < c < 1, d < 0$.
令 $m(x)=\ln g(x)-\ln g(-x)=2 x-\ln (x+1)+\ln (-x+1)=h(x), x \in(-1,1)$,
所以 $m(x)$ 在 $(-1,1)$ 上单调递减, 且 $m(0)=0$,
$\because c \in(0,1), \therefore \ln g(c)-\ln g(-c) < 0, \therefore g(c) < g(-c), \therefore g(d) < g(-c)$,
$\therefore d < -c$, 即 $c+d < 0$, 故选项 B错误;
$\because f(x)=\frac{1}{g(-x)}, \therefore g(-a)=\frac{1}{f(a)}=\frac{100}{101} > 0.99, a \in(-1,0)$,
$\therefore g(-a) > g(d)$, 又 $\because g(x)$ 在 ( $-\infty, 0)$ 上单调递增, $\therefore-a > d, \therefore a+d < 0$, 故选项 C 错误;
由 $\mathrm{C}$ 可知, $g(-b) > g(c),-b \in(0,1)$, 又 $\because g(x)$ 在 $(0,1)$ 上单调递减, $\therefore-b < c, \therefore b+c > 0$, 故选项 D 正确.
故选 AD.
系统推荐